Hydrogel Containing Oleoresin From Copaifera officinalis Presents Antibacterial Activity Against Streptococcus agalactiae - Morguette, Ana Elisa Belotto; Bigotto, Briani Gisele; Varella, Renata de Lima; Andriani, Gabriella Maria; Spoladori, Laís Fernanda de Almeida; Pereira, Patrícia Moraes Lopes; de Andrade, Fabio Goulart; Lancheros, Cesar Armando Contreras; Nakamura, Celso Vataru; Syogo Arakawa, Nilton; Bruschi, Marcos Luciano; Carlos Tomaz, José; et al. (Frontiers in Microbiology, 2019)
Streptococcus agalactiae (Group B Streptococcus - GBS) remains a leading cause of neonatal infections worldwide; and the maternal vaginal-rectal colonization increases the risk of vertical transmission of GBS to neonates and development of infections. This study reports the in vitro antibacterial effect of the oleoresin from Copaifera officinalis Jacq. L. in natura (copaiba oil) and loaded into carbomer-hydrogel against planktonic and sessile cells of GBS. First, the naturally extracted copaiba oil was tested for the ability to inhibit the growth and metabolic activity of planktonic and sessile GBS cells. The time-kill kinetics showed that copaiba oil exhibited a dose-dependent bactericidal activity against planktonic GBS strains, including those resistant to erythromycin and/or clindamycin (minimal bactericidal concentration ranged from 0.06 mg/mL to 0.12 mg/mL). Copaiba oil did not inhibit the growth of different Lactobacillus species, the indigenous members of the human microbiota. The mass spectral analyses of copaiba oil showed the presence of diterpenes, and the kaurenoic acid appears to be one of the active components of oleoresin from C. officinalis related to antibacterial activity against GBS. Microscopy analyses of planktonic GBS cells treated with copaiba oil revealed morphological and ultrastructural alterations, displaying disruption of the cell wall, damaged cell membrane, decreased electron density of the cytoplasm, presence of intracellular condensed material and asymmetric septa. Copaiba oil also exhibited antibacterial activity against established biofilms of GBS strains, inhibiting the viability of sessile cells. Low-cost and eco-friendly carbomer-based hydrogels containing copaiba oil (0.5% - CARB-CO 0.5; 1.0% - CARB-CO 1.0) were then developed. However, only CARB-CO 1.0 preserved the antibacterial activity of copaiba oil against GBS strains. This formulation was homogeneous, soft, exhibited a viscoelastic behavior, and showed good biocompatibility with murine vaginal mucosa. Moreover, CARB-CO 1.0 showed a slow and sustained release of the copaiba oil, killing the planktonic and sessile (established biofilm) cells and inhibiting the biofilm formation of GBS on pre-coated abiotic surface. These results indicate that carbomer-based hydrogels may be useful as topical systems for delivery of copaiba oil directly into de vaginal mucosa and controlling S. agalactiae colonization and infection.